Effect of layer thickness on the overhanging surface quality manufactured by selective laser melting. (May 2022) - Duan, Weipeng; Wu, Meiping; Han, Jitai; Ma, Yiqing; Miao, Xiaojin
With the increasing demand for the precision of lightweight part, overhanging surface quality has attracted more and more attentions in recent years. In this work, the relationship between overhanging surface quality and layer thickness was studied. The testing results revealed that with the increasing of the layer thickness, surface quality, especially the surface flatness, showed a significant decreasing trend due to the decreasing of the bending deformation. When layer thickness was ranged from 0.15 to 0.18, it reached a relative optimal condition while the sinking distance and flatness within 0.095 mm–0.1 mm and 0.076 mm–0.078 mm, respectively. With the further increasing of the layer thickness, both sinking distance and surface flatness had a quite significant decreasing due to the increasing gravity of the overhanging layer powder and bonded powder caused by the molten pool sinking. Combined to the experimental data and the analysis given above, the structure of the overhanging surface was optimized and the surface quality showed a further increase.